Efektivitas Pengelolaan Program Bantuan Nelayan di Dinas Perikanan dan Kelautan Kota Manado - Jericho Danga Pombengi; Joyce Jacinta Rares; Chyntia Malendes; Eklesia Pandei; Joshua Pinontoan; Valentino Lana (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Fisheries assistance programs constitute an important policy instrument to improve the welfare and economic resilience of small-scale fishermen. The effectiveness of these programs is essential to ensure that government interventions generate sustainable socioeconomic benefits for fishing communities. This study aims to analyze the effectiveness of the management of fishermen assistance programs implemented by the Department of Fisheries and Marine Affairs of Manado City in improving fishermen’s welfare. The study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving government officials, program implementers, and fishermen as beneficiaries. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the fishermen assistance program has been implemented continuously and has expanded its beneficiary coverage over time. The program has contributed to supporting fishing activities and improving access to production facilities. However, its effectiveness has not yet reached optimal levels due to several challenges, including inaccuracies in beneficiary targeting, limited technical assistance, low participation of fishermen in planning and evaluation processes, and monitoring mechanisms that remain focused on administrative compliance rather than program outcomes. These limitations reduce the program’s ability to generate sustainable welfare improvements. The study concludes that enhancing program effectiveness requires more accurate beneficiary data, strengthened capacity-building initiatives, participatory governance mechanisms, and impact-based evaluation systems. Program success depends not only on the quantity of assistance distributed but also on the quality of management, implementation, and stakeholder involvement.